Evaluación del potencial insecticida del néctar de Spathodea Campanulata (Bignoniaceae) sobre Sitophilus Zeamais (Coleoptera: Curculionidae) - Franco, Denise Paiva [UNESP]; Guerreiro, Júlio César; Ruiz, Marcelo Gustavo; Da Silva, Regildo Márcio Gonçalves [UNESP] (My University, 2015)
Spathodea campanulata is an ornamental plant species native to Africa introduced to Brazil whose flowers produce large amounts of nectar that is toxic to insects. The aim of this work was to assess the insecticidal potential of S. campanulata nectar through mortality tests performed on Sitophilus zeamais in Assis, São Paulo State, Brazil. The highest sugar concentrations were recorded in nectar harvested from flowers in the evening. Pure nectar spray treatments showed a control efficiency of 89% of the insect population, which was a statistically significant difference as related to other nectar and control treatments.
Evaluation of insecticide potential of Spathodea Campanulata (Bignoniaceae) nectar on Sitophilus Zeamais (Coleoptera: Curculionidae)
Keywords: Control efficiency; Pest; Plant insecticide; Rice weevil; Terpenes